رسول اللہ ﷺکے دفاع میں حضرت ابو طالب کا قصیدہ لامیہ کا تحقیقی جائزہ: Poetry of Abu Talib in the favour of Prophet (P.B.U.H.) - Muddasar Hameed, (MEI, 2023)
When we are talking about life of Peace Be Upon him, it is called “Seerah” and besides that it is called “Sham┐il Nabw┘yah”. In which is described the life of Prophet (peace and blessings of Allah be upon him) as well as the characteristics of your life and your prayers are also mentioned. According to this, many scholars write books which are famous names like Imam Tirmazi, Qazi Ayaz , Ibn-e-Katheer , Allama Sayooti and Mulla Ali Qari. In addition to many books were written on his Characters in after Islam but before Islam have been told many poetries on his “Seerah” and “Shamayil”. In this article described, commented and reviewed the “Shamayil Nabw┘yah” of Peace Be upon him from Dewan-e- Abi Talib.